2021
DOI: 10.1080/10632913.2021.1903640
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of music workshop participation for pupils’ wellbeing and social capital: the In2 music project evaluation

Abstract: This paper reports on the evaluation of the In2 music project in Darlington, England. The project ran for seven weeks from January -March 2020 and involved Year 6 pupils from four primary schools (n = 103) and Year 7 pupils from one secondary school (n = 90), working with Back Chat Brass, a professional brass ensemble. The aim of the In2 music project was to enable pupils to work with professional musicians to enjoy the benefits of group-based music, which include happiness and optimism. These emotions are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For music, dance and visual arts, grouped and separately, the findings showed that cortisol was lower after an arts versus homeroom class at the middle and end of the year, but not at the start of the year. A similar project, where professional musicians worked with school-aged children (Ward et al, 2020) showed through interviews with teachers, musicians, parents and observations that pupils experiencing socioeconomic deprivation enjoyed the benefits of fellowship through group-based music activities. Previously shy pupils began to contribute more in class, and anxious children overcame their fear of performing on stage.…”
Section: Music and Wellbeing In School-aged Participantsmentioning
confidence: 99%
“…For music, dance and visual arts, grouped and separately, the findings showed that cortisol was lower after an arts versus homeroom class at the middle and end of the year, but not at the start of the year. A similar project, where professional musicians worked with school-aged children (Ward et al, 2020) showed through interviews with teachers, musicians, parents and observations that pupils experiencing socioeconomic deprivation enjoyed the benefits of fellowship through group-based music activities. Previously shy pupils began to contribute more in class, and anxious children overcame their fear of performing on stage.…”
Section: Music and Wellbeing In School-aged Participantsmentioning
confidence: 99%
“…For music, dance, and visual arts, grouped and separately, the findings showed that cortisol was lower after an arts versus homeroom class at the middle and end of the year but not at the start of the year. A similar project where professional musicians worked with school aged children (Ward et al, 2020) showed through interviews with teachers, musicians, parents and observations that pupils experiencing socio economic deprivation enjoyed the benefits of fellowship through group based music activities. Previously shy pupils began to contribute more in class, and anxious children overcame their fear of performing on stage.…”
Section: Music and Wellbeing In School Aged Participantsmentioning
confidence: 99%
“…Music therapy also plays a role in people's cognitive, physical, and emotional health; listening to music improves people's mental health through the discipline that exists in the order of different notes and also through words (12) . Also, attending music therapy sessions can provide opportunities for people to create social relationships (13) and leave positive effects on people's mental and physical well-being (14) .…”
Section: Introductionmentioning
confidence: 99%